Blood clot stabilization on root dentin conditioned by the combination of tetracycline and EDTA - Nascimento, Gustavo Giacomelli; Leite, Amauri Antiquera; Leite, Elza Regina Manzolli; Sampaio, José Eduardo Cezar [UNESP]; Leite, Fábio Renato Manzolli (Faculdade de Odontologia de Piracicaba - UNICAMP, 2014)
AIM: To assess the combined use of tetracycline (TTC) and ethylenediaminetetraacetic acid (EDTA) on clot formation, considering that EDTA may neutralize TTC acidity. METHODS: Planed human tooth roots were treated with saline solution, EDTA, TTC and their combination (EDTA followed by TTC and TTC before EDTA). Fresh human blood was applied on the conditioned surfaces to check clot adhesion and stabilization. A previously calibrated (kappa = 0.93) and blinded examiner scored scanning electron micrographs of the samples. Statistical analyses were performed using one-way ANOVA and Tukey's test. RESULTS: Application of TTC before EDTA presented the best results with the highest number of cells adhered to the root surface (p=0.046). Use of EDTA alone and EDTA before TTC disturbed clot stabilization when compared to control group (p<0.01). CONCLUSIONS: The use of TTC before EDTA seems to be able to keep blood cells viable to establish an organized clot and could be used by clinicians together with the conventional mechanical root scaling and planing.
Keywords: ethylenediaminetetraacetic acid; periodontal regeneration; scanning electron microscopy; smear layer